Essential Oils from Plants - Butnariu Monica; Sarac Ioan (Journal of Biotechnology and Biomedical Science, 2018)
Essential oils, called volatile oils or ethereal oils, are natural metabolic secretions of plants, the role of which is not yet fully understood by science. Some specialists consider them to be true plant hormones, fluid manifestations of the immune system of plants, in the sense that they contribute to the removal of pests, attracting, instead, pollinating agents, which are some insects and birds. Small, light–colored spherical structures, is, in fact, modified filaments, which behave like some secretory glands of essential volatile oils. They are the ones who give the fragrance of the aromatic plant and have, in the case of salvation, medicinal curative properties, such as fever reduction, blood cleansing, and relieving pain. Essential oils are products isolated from plants or organs through a physical process that have a certain volatility (higher or lower) and possesses an agreeable odour characteristic of the source from which they originate. They are also known as volatile or essential oils and their name are usually given by the popular name of the plant from which they are extracted. The most important characteristic of these mixtures, which also gives the special economic value, is the specific smell. This is the basis for their use in perfumery, cosmetics and the food industry. Many essential oils have special therapeutic qualities, some of which have been known and used since antiquity.
Keywords: Essential oils